Effects of visual disruption on static and dynamic postural control in people with and without chronic ankle instability - Miao, Yushan; Ge, Yubin; Wang, Dongmei; Mao, Dewei; Song, Qipeng; Wu, Rentana (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: This study aims to determine whether visual disruption could influence static and dynamic postural control in people with and without chronic ankle instability (CAI), with the objective of gaining a comprehensive understanding of the interactions between visual inputs and postural control. Methods: Thirty people with CAI (21 males and 9 females, age=22.0±1.8 years, height=174.4±10.2 cm, body mass=72.5±15.4 kg; Cumberland Ankle Instability Tool (CAIT) score=19.7±1.8) and twenty-nine without CAI (24 males and 5 females, age=22.9±1.6 years, height=172.8±8.0cm, body mass=69.0±11.3 kg; CAIT score=29.0±0.7) were recruited. Their static and dynamic postural control was measured in two conditions with or without visual disruption, simulated using stroboscopic glasses. Static postural control was measured during single-limb standing and represented by root mean square (RMS) of the plantar center of pressure (CoP), dynamic postural control was measured during a Y-balance test and represented by the relative reach distance. Two-way mixed ANOVA (between group: CAI vs non-CAI, within group: normal vision vs visual disruption) was used to analyze data. Results: Significant interactions were detected in the CoP-RMS in the anteroposterior (AP) (p=0.021, η2p=0.090) and mediolateral (ML) (p<0.001, η2p=0.208) directions, and the relative reach distances in the posteromedial (PM) (p=0.023, η2p =0.088) and posterolateral (PL) (p=0.009, η2p=0.113) directions, from normal vision to visual disruption. The CoP-RMS in the AP and ML directions significantly increased and the relative reach distances in the PM and PL directions significantly decreased in people with CAI while remaining unchanged in those without CAI. Conclusion: People with CAI are susceptible to visual disruption on postural control, highlighting the importance of visual input in maintaining stable posture in this population.